Genome‐Wide Polygenic Score Predicts Large Number of High Risk Individuals in Monogenic Undiagnosed Young Onset Parkinson's Disease Patients from India. Issue 11 (10th July 2022) - Kukkle, Prashanth Lingappa; Geetha, Thenral S.; Chaudhary, Ruchi; Sathirapongsasuti, Jarupon F.; Goyal, Vinay; Kandadai, Rukmini Mridula; Kumar, Hrishikesh; Borgohain, Rupam; Mukherjee, Adreesh; Oliver, Merina; Sunil, Meeta; Mootor, Mohammed Faizal Eeman; et al.
Abstract: Parkinson's disease (PD) is a genetically heterogeneous neurodegenerative disease with poorly defined environmental influences. Genomic studies of PD patients have identified disease‐relevant monogenic genes, rare variants of significance, and polygenic risk‐associated variants. In this study, whole genome sequencing data from 90 young onset Parkinson's disease (YOPD) individuals are analyzed for both monogenic and polygenic risk. The genetic variant analysis identifies pathogenic/likely pathogenic variants in eight of the 90 individuals (8.8%). It includes large homozygous coding exon deletions in PRKN and SNV/InDels in VPS13C, PLA2G6, PINK1, SYNJ1, and GCH1 . Eleven rare heterozygous GBA coding variants are also identified in 13 (14.4%) individuals. In 34 (56.6%) individuals, one or more variants of uncertain significance (VUS) in PD/PD‐relevant genes are observed. Though YOPD patients with a prioritized pathogenic variant show a low polygenic risk score (PRS), patients with prioritized VUS or no significant rare variants show an increased PRS odds ratio for PD. This study suggests that both significant rare variants and polygenic risk from common variants together may contribute to the genesis of PD. Further validation using a larger cohort of patients will confirm the interplay between monogenic and polygenic variants and their use in routine genetic PD diagnosis and risk assessment. Abstract : Here young onset Parkinson patients are investigated using whole genome sequencing. They suggest that both significant rare variants and polygenic risk from common variants together contribute to the genesis of Parkinson disorder. After including polygenic risk, the diagnosis rate improves from 8.8% to 28.8%.